Genetic Modifiers for the Long-QT Syndrome: How Important Is the Role of Variants in the 3′ Untranslated Region of KCNQ1?. (August 2016) - Crotti, Lia; Lahtinen, Annukka M.; Spazzolini, Carla; Mastantuono, Elisa; Monti, Maria Cristina; Morassutto, Caterina; Parati, Gianfranco; Heradien, Marshall; Goosen, Althea; Lichtner, Peter; Meitinger, Thomas; Brink, Paul A.; et al.
Abstract : Background—: Long-QT syndrome is an inherited cardiac channelopathy characterized by delayed repolarization, risk of life-threatening arrhythmia, and significant clinical variability even within families. Three single-nucleotide polymorphisms (SNPs) in the 3′ untranslated region of KCNQ1 were recently suggested to be associated with suppressed gene expression and hence decreased disease severity when located on the same haplotype with a disease-causing KCNQ1 mutation. We sought to replicate this finding in a larger and a genetically more homogeneous population of KCNQ1 mutation carriers. Methods and Results—: The 3 SNPs (rs2519184, rs8234, and rs10798) were genotyped in a total of 747 KCNQ1 mutation carriers with A341V, G589D, or IVS7-2A>G mutation. The SNP haplotypes were assigned based on family trees. The SNP allele frequencies and clinical severity differed between the 3 mutation groups. The different SNP haplotypes were neither associated with heart rate–corrected QT interval duration (QTc) nor cardiac events in any of the 3 mutation groups. When the mutation groups were combined, the derived SNP haplotype of rs8234 and rs10798 located on the same haplotype with the mutation was associated with a shorter QTc interval ( P <0.05) and a reduced occurrence of cardiac events ( P <0.01), consistent with the previous finding. However, when the population-specific mutation was controlled for, both associations were no longer evident. Conclusions—: 3′ Untranslated region SNPs are not acting as genetic modifiers in a large group of LQT1 patients. The confounding effect of merging a genetically and clinically heterogeneous group of patients needs to be taken into account when studying disease modifiers. Abstract : Supplemental Digital Content is available in the text.